A Cotton Lignin Biosynthesis Gene, GhLAC4, Fine-Tuned by ghr-miR397 Modulates Plant Resistance Against Verticillium dahliae - Wei, Taiping; Tang, Ye; Jia, Pei; Zeng, Yanming; Wang, Bingting; Wu, Pan; Quan, Yonggang; Chen, Aimin; Li, Yucheng; Wu, Jiahe (Frontiers in Plant Science, 2021)
ABSTRACT Plant lignin is a component of the cell wall, and plays important roles in the transport potential of water and mineral nutrition and plant defense against biotic stresses. Therefore, it is necessary to identify lignin biosynthesis-related genes and dissect their functions and underlying mechanisms. Here, we characterised a cotton LAC, GhLAC4, which participates in lignin biosynthesis and plant resistance against Verticillium dahliae. According to degradome sequencing and GUS reporter analysis, ghr-miR397 was identified to directedly cleave the GhLAC4 transcript through base complementary. GhLAC4 knockdown and ghr-miR397 overexpression significantly reduced basal lignin content compared to the control, whereas ghr-miR397 silencing significantly increased basal lignin levels. Based on staining patterns and GC/MS analysis, GhLAC4 acted in G-lignin biosynthesis. Under V. dahliae infection, we found that G-lignin content in ghr-miR397-knockdowned plants significantly increased, compared to these plants under the mock treatment, while G-lignin contents in GhLAC4-silenced plants and ghr-miR397-overexpressed plants treated with pathogen were comparable with these plants treated with mock, indicating that GhLAC4 participates in defense-induced G-lignin biosynthesis in the cell wall. Knockdown of ghr-miR397 in plants inoculated with V. dahliae promoted lignin accumulation and increased plant resistance. The overexpression of ghr-miR397 and knockdown of GhLAC4 reduced lignin content and showed higher susceptibility of plants to the fungal infection compared to the control. The extract-free stems of ghr-miR397-knockdowned plants lost significantly less weight when treated with commercial cellulase and V. dahliae secretion compared to the control, while the stems of ghr-miR397-overexpressed and GhLAC4-silenced plants showed significantly higher loss of weight. These results suggest that lignin protects plant cell walls from degradation mediated by cellulase or fungal secretions. In summary, the ghr-miR397-GhLAC4 module regulates both basal lignin and defense-induced lignin biosynthesis and increases plant resistance against infection by V. dahliae.